Right atrial cardiac lipoma with distinctive imaging characteristics. A rare case report and literature review - Chen, Qiqing; Yang, Dayan; Liu, Lili; Jing, Xiangxiang (Frontiers in Cardiovascular Medicine, 2022)
Cardiac lipomas are rare primary cardiac tumors that are often only detected incidentally during other examinations. Lipomas of the right atrium are particularly rare. In this report, we describe the case of a patient presenting with a mixed cystic-solid lipoma in the right atrium. The symptoms, imaging findings, and treatment strategies associated with this case are discussed herein. This 65-year-old female patient reported to our hospital due to exertional chest tightness, shortness of breath, and occasional chest pain for over 1 year. She subsequently underwent transthoracic echocardiography and contrast-enhanced ultrasonography, both of which revealed a cystic-solid mass in the right atrium. The transthoracic computed tomography scan showed a dense patchy shadow in the right atrium. The mass was completely excised from the atrial septum, and subsequent histopathological examination confirmed its identity as a lipoma. Surgical resection remains the primary treatment approach for cardiac lipomas, and multimodal imaging is of key importance for the diagnosis and follow-up monitoring of affected patients.